Предмет: Алгебра,
автор: Lobster177
(y-4)(y+2)+(3-y)^2-2(7+y)(y-7)
Ответы
Автор ответа:
0
= Y^2 + 2Y - 4Y - 8 + 9 - 6Y + Y^2 - 2 * ( 7Y - 49 + Y^2 - 7Y ) =
= 2Y^2 - 8Y + 1 - 2 * ( Y^2 - 49 ) =
= 2Y^2 - 8Y + 1 - 2Y^2 + 98 =
= - 8Y + 99
= 2Y^2 - 8Y + 1 - 2 * ( Y^2 - 49 ) =
= 2Y^2 - 8Y + 1 - 2Y^2 + 98 =
= - 8Y + 99
Автор ответа:
0
y^2+2y-4y-8+9-6y+^2-(14+2y)(y-7)
4y^2-36y+99=0 дальше сам
4y^2-36y+99=0 дальше сам
Похожие вопросы
Предмет: Алгебра,
автор: anarakaziyeva
Предмет: Русский язык,
автор: arturkamilov08
Предмет: Информатика,
автор: adiyattoleubai7
Предмет: Физика,
автор: zhenyalyceum
Предмет: Биология,
автор: biolicei2